Late-onset Candida keratitis after Descemet stripping automated endothelial keratoplasty : clinical and confocal microscopic report - Ortiz-Gomariz, Amanda (2011)
Purpose. To report clinical and confocal microscopy features of late-onset Candida albicans keratitis after Descemet stripping automated keratoplasty (DSAEK). Methods. We performed clinical and confocal scan on a patient who underwent DSAEK and phacoemulsification for Fuchs endothelial dystrophy and cataract. Results. A 76-year-old woman who underwent uneventful DSAEK and phacoemulsification presented with white to cream deposits 3 months after DSAEK. Confocal microscopy showed a hyperintense deposit at the lenticule and interface. Confocal scan also disclosed intense haze and inflammation at the interface and clusters of hyperreflective round structures resembling epithelial cells within the interface area. No signs of hyphae-like structures were seen. Late-onset symptoms misled us into a bacterial chronic endophthalmitis diagnosis, and the patient was started on topical and systemic antibiotics. Despite intense antibiotic therapy, the patient developed severe endophthalmitis, so we performed anterior vitrectomy and the donor lenticule was removed. Microbiology results from the removed lenticule showed infection by C albicans. Antifungal therapy with systemic and topical voriconazole controlled the infection. Conclusions. Candida interface keratitis is possible after DSAEK. The posterior location of infected tissue poses diagnostic and therapeutic challenges. In our case, the late onset of the symptoms and not performing corneoscleral rim cultures delayed correct diagnosis. This is the first reported case of post-DSAEK Candida keratitis with confocal microscopy images. A hyperintense granular deposit was seen at the lenticule and interface with confocal microscopy. We also observed intense haze, granular round structures resembling epithelial cells, and hyperreflective needle-shaped material at the interface. No hyphae-like structures were seen with confocal imaging.